Kant after Duchamp - De Duve, Thierry (Cambridge : MIT press, 1996)
Nauman, Bruce ; Levine, Sherrie ; Duchamp, Marcel ; Richter, Gerhard ; Frize, Bernard ; Ryman, Robert ; Beuys, Joseph ; Snow, Michael ; Kelley, Mike ; Broodthaers, Marcel ; Fischli & Weiss ; Blocher, Sylvie
boek
Keywords: Kant, Immanuel; Duchamp, Marcel